Improving lifestyles sustainability through community gardening: results and lessons learnt from the JArDinS quasi-experimental study - Marion Tharrey; Ashby Sachs; Marlène Perignon; Chantal Simon; Caroline Mejean; Jill Litt; Nicole Darmon (BMC, 2020)
Abstract Background Despite an increasing number of studies highlighting the health benefits of community gardening, the literature is limited by cross-sectional designs. The "JArDinS" quasi-experimental study aimed to assess the impact of community garden participation on the adoption of more sustainable lifestyles among French adults. Methods Individuals entering a community garden in Montpellier (France) in 2018 (n = 66) were compared with pairwise matched individuals with no experience in community gardening (n = 66). Nutritional quality, environmental impact and cost of monthly household food supplies, level of physical activity measured by accelerometers, as well as mental and social well-being, sensitivity to food waste, and connection with nature were evaluated at baseline (t0) and 12 months later (t1) to explore sustainability of lifestyles in social/health, environmental and economic dimensions. Linear mixed models were used to determine the independent effect of community gardening on investigated lifestyles components. In-depth interviews were conducted at t1 with 15 gardeners to better understand changes that may have occurred in gardeners' lives during the first year of gardening. Results At t0, gardeners had lower education level, lower BMI and their household reported lower percentage of meals consumed outside of the home compared to non-gardeners (p <  0.05). Participating in the community garden had no significant impact, in spite of sufficient statistical power, on fruit and vegetables supplies (main outcome), nor on physical activity parameters, nor on others of the social/health, environmental and economic lifestyles components investigated. Qualitative interviews suggested the existence of pre-established health and environmental consciousness in some gardeners and revealed several barriers to the participation such as lack of time, lack of gardening knowledge, physical difficulty of gardening, health problems and conflicts with other gardeners. Conclusions The health benefits of community gardening previously reported by cross-sectional studies might be confounded by selection bias. The JArDinS study highlights the need to identify solutions to overcome barriers related to community garden participation when designing relevant public health interventions for the promotion of sustainable lifestyles. Trial registration The study was registered at clinicaltrials.gov as NCT03694782 . Date of registration: 3rd October 2018, retrospectively registered.